1962
DOI: 10.4141/cjps62-034
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Leaf Levels of Nitrogen, Phosphorus and Potassium in Sweet Corn and Snap Beans

Abstract: Optimum nutrient levels were derived by comparing the polynomial tegression curves relating leaf analyses and crop yields with rates of applied nitrogen, phosphorus and potassium. IJppermost mature leaves were used for analysis, and samples ivere collected-it specific physiological stages of development.In two seasons the optimum ler,-els in sweet corn difiered by 7,25 a.nd 9 per ccnt, and in snap beans by 12. 29 end 1l per cent for nitrogen. phosphorus and potassium resp.ectivel)'. A lorv moisture supply was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1962
1962
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Critical concentrations for P in wheat were increased by low root temperature (Sheppard et al, 1986) and increases in requirement for K have been found with soil moisture deficits and limiting supplies of Mg and Na (Mackay and Leefe, 1962;Smith et al, 1982). In the present paper we examine the influence of low root temperature on the K requirements of young tomato plants grown with adequate and limiting supplies of the element.…”
Section: Introductionmentioning
confidence: 86%
“…Critical concentrations for P in wheat were increased by low root temperature (Sheppard et al, 1986) and increases in requirement for K have been found with soil moisture deficits and limiting supplies of Mg and Na (Mackay and Leefe, 1962;Smith et al, 1982). In the present paper we examine the influence of low root temperature on the K requirements of young tomato plants grown with adequate and limiting supplies of the element.…”
Section: Introductionmentioning
confidence: 86%
“…The direct effects of fertilizer application rates on yields and nutrient uptake are described in another paper (11). Only the interaction effects of irriEation and fertilizer treatments on vields and nutrient content of the crJps will be considered here.…”
Section: Effect Of Lrrigation On F'ertilizer Utilizationmentioning
confidence: 99%
“…However, the decreases in shoot nutrient concentrations with many biochar treatments may be predictive of eventual growth reductions because the concentrations generally were below nutrient sufficiency concentration ranges for these crops even without the addition of biochar ( Table 5 ) ( Hanlon & Hochmuth, 2000 ; Hartz, Johnstone, Williams, & Smith, 2007 ; MacKay & Leefe, 1962 ; Mueller, 2019 ). Decreases in shoot N were more significant for the manure-based biochars (SS and PL) and blends (55 and 82) than for the cellulosic biochars.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced growth with biochar treatments containing animal manure (55, 82, SS, and PL) was likely due to a Nenhancing (Clough et al, 2013) and a general nutrientenhancing effect (Agegnehu et al, 2017) because the initial soil levels of N, P, and K appeared to be low (Table 1) and the levels of these elements high in the at least partially manure-based biochars (Table 2). However, the decreases in shoot nutrient concentrations with many biochar treatments may be predictive of eventual growth reductions because the concentrations generally were below nutrient sufficiency concentration ranges for these crops even without the addition of biochar (Table 5) (Hanlon & Hochmuth, 2000;Hartz, Johnstone, Williams, & Smith, 2007;MacKay & Leefe, 1962;Mueller, 2019). Decreases in shoot N were more significant for the manure-based biochars (SS and PL) and blends (55 and 82) than for the cellulosic biochars.…”
Section: Effects Of Biochar On Shoot Nitrogenmentioning
confidence: 99%